2018
DOI: 10.1016/j.ygyno.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics associated with long-term survival in advanced epithelial ovarian cancer: an NRG Oncology/Gynecologic Oncology Group ancillary data study

Abstract: Objective To identify clinicopathologic factors associated with 10-year overall survival in epithelial ovarian cancer (EOC) and primary peritoneal cancer (PPC), and to develop a predictive model identifying long-term survivors. Methods Demographic, surgical, and clinicopathologic data were abstracted from GOG 182 records. The association between clinical variables and long-term survival (LTS) (>10 years) was assessed using multivariable regression analysis. Bootstrap methods were used to develop predictive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 32 publications
(35 reference statements)
2
35
2
Order By: Relevance
“…We used forwardselection to build the model and retained all variables with a P < 0.3. We decided a priori that age, stage, and CA-125 level at diagnosis would be in the final model as these factors have been previously reported to be associated with survival among ovarian cancer cases (5,6). We computed the Elixhauser comorbidity score (7) for each case and included individual components of the score in the model-building process if at least 20 patients had the condition.…”
Section: Methodsmentioning
confidence: 99%
“…We used forwardselection to build the model and retained all variables with a P < 0.3. We decided a priori that age, stage, and CA-125 level at diagnosis would be in the final model as these factors have been previously reported to be associated with survival among ovarian cancer cases (5,6). We computed the Elixhauser comorbidity score (7) for each case and included individual components of the score in the model-building process if at least 20 patients had the condition.…”
Section: Methodsmentioning
confidence: 99%
“…A study of the California Cancer Registry on 11 541 ovarian cancer patients among all histological subtypes and stages identified a total of 3583 patients (31%) who survived more than 10 years and, of these, 32.4% had stage III/IV disease. Similarly, a retrospective analysis of the Gynecologic Cancer Intergroup GOG182‐ICON5 trial on advanced‐stage EOC identified 195 of 3010 patients who survived more than 10 years; 76% of these had serous histology . These studies illustrate that long‐term survival occurs in high‐risk ovarian cancer.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, a retrospective analysis of the Gynecologic Cancer Intergroup GOG182-ICON5 trial on advanced-stage EOC identified 195 of 3010 patients who survived more than 10 years; 76% of these had serous histology. 13 These studies illustrate that long-term survival occurs in high-risk ovarian cancer. To date, detailed analysis of clinical data or histopathological and molecular characterisations are only sparse (for review see Hoppenot et al 10 ), but offer great potential to deepen our understanding of tumour progression and chemosensitivity of HGSC.…”
Section: Introductionmentioning
confidence: 94%
“…9 Factors associated with long-term survival included the following: endometrioid histology, stage III (vs stage IV), absence of ascites, preoperative disease distribution score, optimal microscopic cytoreduction, and lower surgical complexity score. Among a subset of 3010 patients enrolled in GOG 0182, a total of 195 patients (6.5%) survived longer than 10 years.…”
Section: Primary Therapymentioning
confidence: 99%
“…Among a subset of 3010 patients enrolled in GOG 0182, a total of 195 patients (6.5%) survived longer than 10 years. 9 Factors associated with long-term survival included the following: endometrioid histology, stage III (vs stage IV), absence of ascites, preoperative disease distribution score, optimal microscopic cytoreduction, and lower surgical complexity score. However, the combined model fell short of predefined clinical utility boundaries, and the authors concluded that the addition of tumor molecular profiles should be considered.…”
Section: Primary Therapymentioning
confidence: 99%